Kyasanur Forest Disease (KFD): Rare Disease of Zoonotic Origin - Muraleedharan, Manju (Journal of Nepal Health Research Council, 2017)
Kyasanur forest disease (KFD) is a rare tick borne zoonotic disease that causes acute febrile hemorrhagic illness in humans and monkeys especially in southern part of India. The disease is caused by highly pathogenic KFD virus (KFDV) which belongs to member of the genus Flavivirus and family Flaviviridae. The disease is transmitted to monkeys and humans by infective tick Haemaphysalisspinigera. Seasonal outbreaks are expected to occur during the months of January to June. The aim of this paper is to briefly summarize the epidemiology, mode of transmission of KFD virus, clinical findings, diagnosis, treatment, control and prevention of the disease..Keywords: Flavivirus; India; kyasanur forest disease; monkey fever; ticks.